17 beta-estradiol hydroxylation catalyzed by human cytochrome P450 1B1. - Hayes, C L (1996)
The 4-hydroxy metabolite of 17 beta-estradiol (E2) has been implicated in the carcinogenicity of this hormone. Previous studies showed that aryl hydrocarbon-receptor agonists induced a cytochrome P450 that catalyzed the 4-hydroxylation of E2. This activity was associated with human P450 1B1. To determine the relationship of the human P450 1B1 gene product and E2 4-hydroxylation, the protein was expressed in Saccharomyces cerevisiae. Microsomes from the transformed yeast catalyzed the 4- and 2-hydroxylation of E2 with Km values of 0.71 and 0.78 microM and turnover numbers of 1.39 and 0.27 nmol product min-1.nmol P450-1, respectively. Treatment of MCF-7 human breast cancer cells with the aryl hydrocarbon-receptor ligand indolo[3,2-b]carbazole resulted in a concentration-dependent increase in P450 1B1 and P450 1A1 mRNA levels, and caused increased rates of 2-, 4-, 6 alpha-, and 15 alpha-hydroxylation of E2. At an E2 concentration of 10 nM, the increased rates of 2- and 4-hydroxylation were approximately equal, emphasizing the significance of the low Km P450 1B1-component of E2 metabolism. These studies demonstrate that human P450 1B1 is a catalytically efficient E2 4-hydroxylase that is likely to participate in endocrine regulation and the toxicity of estrogens.